Isotope Tracing of the Parana River, Argentina - Panarello, Hector Osvaldo (2012)
The Rio de la Plata estuary is the collector of a vast drainage basin of about 3.1x106 km2 . There are many tributaries to the estuary but the Parana and Uruguay rivers directly discharge more than 99% of the average discharge (24 000 m3/s). The stable isotope composition of water in this estuary has been monitored since 1997. From 120 isotopic pairs, it could be established that 18O and 2H exhibit a cyclical pattern with a maximum in November and a minimum in May. Values correspond to the ITCZ position. When it is located near 8oN, the amount of precipitation over the basin decreases and hence the isotopic composition of both elements is more positive. Conversely, when the ITCZ moves southward, the pluviosity increases, leading to more negative δ18O and δ2H values. This isotopic signal is recordered with a delay of ca 4 month in the estuary. The derivate magnitude, deuterium excess, showed important variations, from 1 to δ18 per mille, with the higher values being related to positive ENSO (El Nino) phases and lower values to negative ENSO (La Nina). Despite the interactions with groundwater and physical processes along ca. 2800 km, the Parana River still reflects at its mouth all these climatic phenomena that control the δ2H and δ18O contents at its catchment areas.